Aspects of memory acts: transnational cultural memory and ethics - Steffi Hobuß (Journal of Aesthetics & Culture, 2011)
In the paper I use arguments from Ludwig Wittgenstein, John L. Austin and Judith Butler to show how the concepts of collective memory and of performativity can help to formulate some ideas about what an ethics of memory can deal with. The positions of speakers or agents and the question of responsibility play a fundamental role in this argument.